Development of local strontium ranelate delivery systems and long term in vitro drug release studies in osteogenic medium. Issue 1 (December 2018) - Loca, Dagnija; Smirnova, Anastasija; Locs, Janis; Dubnika, Arita; Vecstaudza, Jana; Stipniece, Liga; Makarova, Elina; Dambrova, Maija
Abstract It has been recognized that the operative stabilization of osteoporotic fractures should be followed up with an appropriate osteoporosis treatment in order to decrease the risk of repeated fractures. Despite the good clinical results of strontium ranelate (SrRan) towards the osteoporosis treatment, high drug doses and long treatment period cause an increased risk of serious side effects. Novel local SrRan/poly(lactic acid) (SrRan/PLA) delivery systems containing from 3.57 ± 0.28 wt% to 24.39 ± 0.91 wt% of active substance were developed. In order to resemble the naturally occurring processes, osteogenic media (OM) was used as a release medium for long term (121 days)in vitro drug release studies and UV/VIS method for the determination of SrRan content in OM was developed and validated. Biomimetic calcium phosphate precipitates were found on the surface and in the pores of prepared delivery system after microcapsule exposure to OM for 121 days as well as SrRan particles, indicating that the release of the drug have not been completed within 121 days.In vitro cell viability evaluation approved no cytotoxic effects of microcapsule suspensions and extracts.